AN UNUSUALLY DELAYED CASE OF PRE CERVICAL RIGHT UTERINE TORSION IN A NON-DESCRIPTIVE BUFFALO - NESANURU, N.SAI HEMACHAND; K, Jyothi; Sai Gunaranjan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
A non descriptive buffaloe in its second parity and in advanced gestation presented with the history of recurrent bloat, scanty faeces, straining during defaecation and urination since one month. Animal showed a stiff, stilted gait and per vaginal and per rectal exploration revealed the left broad ligament crossing over the top of the twisted portion of the birth canal which confirmed right sided pre-cervical uterine torsion. Rolling of the animal was unsuccessful and animal succumbed to death after two days.